IMPLEMENTASI KURIKULUM TAHFIZH AL QURAN DI SEKOLAH DASAR ISLAM - Siti Halimah; Syaukani Syaukani; Mhd. Fauzan Habibi Parinduri (JP : JURNAL PENDIDIKAN, 2022)
Abstract: This research is meant to describe the implementation of tahfizh al Quran curriculum which includes planning, implementation, methods and media that used. This research used qualitative research method with naturalistic approach. This research was conducted at Mawaddah Warohmah Integrated Islamic Elementary School Medan. The main participants in this study were the coordinator or supervisor teacher of tahfizh alQuran at Mawaddah Warohmah Integrated Islamic Elementary School Medan. The results of this study is the implementation of tahfizh alQuran curri- culum in Islamic Elementary School which includes: 1) Planning of learning curriculum tahfizh al Quran has been prepared in the form of lesson plan, 2) Imple- mentation of learning tahfizh alQuran begins with read of study prayer, after that read Asmaul Husna and continued with memorization and muraja'ah alQuran guided by homeroom teachers with the method of sima'i, group and talaqqi, and 4) The media that used such as form of print, audio and visual media. Keywords: tahfizh al Quran, curriculum, school